2019
DOI: 10.2176/nmccrj.cr.2018-0242
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sacral Perineurial Cysts Presented Symptoms Triggered by Nonaneurysmal Perimesencephalic Subarachnoid Hemorrhage

Abstract: The origin and pathogenesis of perineurial cysts remain unclear. Here, we report a rare case of multiple sacral perineurial cysts presented symptoms triggered by nonaneurysmal perimesencephalic subarachnoid hemorrhage (SAH). A 48-year-old male presented with a severe headache of sudden onset. Brain computed tomography revealed a SAH in the basal cistern; however, no abnormal vascular lesion was detected. Four days after the onset of the SAH, he suffered from left buttock pain, followed by urinary dysfunction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…When the cyst fills with fluid, such as CSF or blood, the adjacent neural or body structure is compressed and pain develops. Pain after hemorrhage in the cysts is associated with SAH after rupture of a cerebral aneurysm [6] . In the present case, although SAH secondary to rupture of a cerebral aneurysm was not identified, the intra-cyst hematoma likely expanded the lesion, leading to clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…When the cyst fills with fluid, such as CSF or blood, the adjacent neural or body structure is compressed and pain develops. Pain after hemorrhage in the cysts is associated with SAH after rupture of a cerebral aneurysm [6] . In the present case, although SAH secondary to rupture of a cerebral aneurysm was not identified, the intra-cyst hematoma likely expanded the lesion, leading to clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Yamagami, [38] 2019 Nishimura et al, [23] Tokgöz et al, [34] Serratrice et al, [29] 2022 L5-S3 cyst with epidermoid in a 42-year-old woman was reported in year 2020. e case becomes more interesting when it is revealed that the epidermoid is Iatrogenic and acquired.…”
Section: Keitaromentioning
confidence: 99%
“…A review of the literature on Tarlov cysts showed that of the total 39 cases, the majority were females [Tables 1 and 2]. [30][31][32][33][35][36][37][38][39] ey are attributed to either musculoskeletal defects (supported by Tarlov cysts in collagen disorders like Marfan) that enlarge due to the hydrodynamic forces of CSF (i.e., continuous or pulsatile). In this series, patients averaged 40.35 years of age with a female threefold predominance.…”
Section: Keitaromentioning
confidence: 99%